Sifat Relasi pada Ruang Barisan (N ̅,q) - Salwa; Aini, Qurratul (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Sequence space is one of the topics that is often researched by researchers in the field of mathematical analysis. Such as the properties of its completeness and the relation between the sequence spaces. However, this study aims to see how the proerties of the relation in the sequence space and its dual β. This research determine several theorems related to the relation between the sequence space with its dual β.